Inside Back Cover: Mass Spectrometry Imaging Reveals In Situ Behaviors of Multiple Components in Aerosol Particles (Angew. Chem. Int. Ed. 43/2021). Issue 43 (9th August 2021) - Jiang, Yuming; Sun, Jie; Xiong, Caiqiao; Liu, Huihui; Li, Yuze; Wang, Xiao; Nie, Zongxiu
Abstract : A novel mass spectrometry imaging strategy to trace and quantify carbonaceous particles in situ is reported by Jie Sun, Caiqiao Xiong, Zongxiu Nie et al. in their Research Article on page 23225 . The method provides not only the spatial biodistribution of carbonaceous aerosol at sub‐organ level, but also chemical information on multiple components from these particles based on their intrinsic fingerprints upon laser ablation. This work provides a new opportunity to understand how ambient particles translocate and release their surface organic matter in vivo.